The ancient aesthetics of deception: the ethics of enchantment from Gorgias to Heliodorus - Grethlein, Jonas (Cambridge University Press, 2021)
"The concept of mimēsis has dominated reflection on the nature and role of representation in Greek literature. Jonas Grethlein, in his ambitious new book, takes this reflection a step further. He argues that, beyond mimēsis, there was an important but unacknowledged strand of reflection focused instead on the nuanced idea of apatē (often translated into English as 'deceit'), oscillating between notions of 'deception' and 'aesthetic illusion'. Many authors from Gorgias and Plato to Philo, Plutarch and Clement of Alexandria used this key concept to entwine aesthetics with ethics. In creatively exploring the various reconfigurations of apatē, and placing these in their socio-historical contexts, the book offers a bold new history of ancient aesthetics. It also explores the present significance of the aesthetics of deception, unlocking the potential of ancient reflection for current debates on the ethical dimension of representation. It will appeal to scholars in classics and literary theory alike"--
Includes bibliographical references and index
Keywords: Täuschung; Literatur; Griechisch